Intravenous Infection of Small Ruminants Suggests a Goat-Restricted Host Tropism and Weak Humoral Immune Response for an Atypical Bluetongue Virus Isolate - Massimo Spedicato; Giovanni Di Teodoro; Liana Teodori; Mariangela Iorio; Alessandra Leone; Barbara Bonfini; Lilia Testa; Maura Pisciella; Claudia Casaccia; Ottavio Portanti; Emanuela Rossi; Tiziana Di Febo; et al. (Viruses, 2023)
Bluetongue virus (BTV) is the etiologic agent of bluetongue (BT), a viral WOAH-listed disease affecting wild and domestic ruminants, primarily sheep. The outermost capsid protein VP2, encoded by S2, is the virion’s most variable protein, and the ability of reference sera to neutralize an isolate has so far dictated the differentiation of 24 classical BTV serotypes. Since 2008, additional novel BTV serotypes, often referred to as “atypical” BTVs, have been documented and, currently, the full list includes 36 putative serotypes. In March 2015, a novel atypical BTV strain was detected in the blood of asymptomatic goats in Sardinia (Italy) and named BTV-X ITL2015. The strain re-emerged in the same region in 2021 (BTV-X ITL2021). In this study, we investigated the pathogenicity and kinetics of infection of BTV-X ITL2021 following subcutaneous and intravenous infection of small ruminants. We demonstrated that, in our experimental settings, BTV-X ITL2021 induced a long-lasting viraemia only when administered by the intravenous route in goats, though the animals remained healthy and, apparently, did not develop a neutralizing immune response. Sheep were shown to be refractory to the infection by either route. Our findings suggest a restricted host tropism of BTV-X and point out goats as reservoirs for this virus in the field.